Hubungan Kebiasaan Sarapan Pagi dengan Status Gizi dan Kejadian Anemia pada Remaja Putri di Fakultas Ilmu Kesehatan Universitas Muhammadiyah Surakarta - Nabila Anindita Nareswari; M. Muwakhidah (Yayasan Literasi Sains Indonesia, 2025)
Adolescence is a crucial period in life, therefore this period is considered vulnerable and has significant health risks. One of the nutritional problems experienced by adolescents is anemia. Anemia can occur because the number of red blood cells or hemoglobin levels in red blood cells is lower than normal. This study used an observational method with a cross-sectional approach. This study was conducted in April 2025. The population in this study were all female students of the Faculty of Health Sciences, Muhammadiyah University of Surakarta Class of 2023, totaling 88 samples, this study used a simple random sampling technique. The results showed that the majority of respondents were from the nutrition science study program (29.0%) and the majority were 20 years old (42.0%). Most respondents were not accustomed to eating breakfast (58.0%) with an intake percentage of 25%. In terms of nutritional status, 43.0% of respondents were in the normal nutritional category, 32.0% were overweight, and 25% were classified as malnourished. Regarding hemoglobin levels, as many as 51.0% of respondents had anemia, and 49.0% were classified as not anemic. Based on the analysis results, a relationship was found between breakfast habits and nutritional status and the incidence of anemia in female adolescents at the Faculty of Health Sciences, Muhammadiyah University of Surakarta.